2013
DOI: 10.20870/oeno-one.2013.47.2.1543
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of salinity effects on ionic balance and compatible solutes in nine Iranian table grape (<em>Vitis vinifera</em> L.) genotypes

Abstract: <p style="text-align: justify;"><strong>Aim</strong>: To study the salinity tolerance of own rooted grape cuttings taken from nine table grape (<em>Vitis vinifera</em> L.) genotypes growing in the Urmia Salt Lake region (Iran): LaaleBidaneh, Gharashani, Sachagh, Shahroodi, LaaleSefid, Khalili, Chawga, GhezelUzum and Gharagandomeh.</p><p style="text-align: justify;"><strong>Methods and results</strong>: Plants were treated with nutrient solutions containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…Under saline conditions in some plants, particularly in grapevines, sodium remains in the roots and stems and chloride accumulated in the shoots. Therefore, control of Cltransport and Clexclusion from shoots is correlated with salt tolerance (Mohammadkhani et al, 2013). In our study, GharaUzum and Keshmeshi had respectively lower and higher Claccumulation in petioles and lamina at 100 mM NaCl.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Under saline conditions in some plants, particularly in grapevines, sodium remains in the roots and stems and chloride accumulated in the shoots. Therefore, control of Cltransport and Clexclusion from shoots is correlated with salt tolerance (Mohammadkhani et al, 2013). In our study, GharaUzum and Keshmeshi had respectively lower and higher Claccumulation in petioles and lamina at 100 mM NaCl.…”
Section: Discussionsupporting
confidence: 49%
“…Others have challenged the value of these solutes as positive indicator for resistance to salt stress. Mohammadkhani et al, (2013) reported that hyper accumulation of soluble sugars is not essential for improving salinity tolerance in grapevines and it is just a symptom of salt stress. The soluble sugar content in roots and laminas increased with increasing salinity in all of our genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study four grape genotypes were compared from the view point of phenolic compounds under salinity. In previous experiments 18 grape genotypes was screened based on salinity tolerance (Mohammadkhani et al 2013(Mohammadkhani et al , 2014. The genotypes with higher (Gharashani and H6) and lower (Shirazi and GhezelUzum) salinity tolerance selected for determining phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the expression of genes associated with salinity tolerance was compared in four grape genotypes. In previous experiments we screened 18 grape genotypes from the viewpoint of salt-tolerance parameters (Mohammadkhani et al, 2013(Mohammadkhani et al, , 2014. Genotypes with lower (GhezelUzum and Shirazi) and higher (H6 and Gharashani) capacity for salinity tolerance were selected for molecular analysis.…”
Section: Salinity Effects On Expression Of Phenylpropanoid Pathway Genesmentioning
confidence: 99%